Delay factors and operational performance of bus rapid transit systems: A systematic literature review with insights for Indonesia - Hazmi, Ervaby Jati Al; Setiadji, Bagus Hario (Edelweiss Applied Science and Technology, 2025)
Bus Rapid Transit (BRT) systems are designed to enhance urban mobility through fast, reliable, and cost-efficient services; however, operational delays continue to undermine system performance and user confidence. Purpose: This study systematically reviews global and Indonesian literature to identify key delay factors and synthesize operational performance metrics relevant to BRT systems. Design/Methodology/Approach: A PRISMA-based Systematic Literature Review (SLR) of 104 publications (2000–2025) was conducted through identification, screening, eligibility assessment, and thematic synthesis. Findings: Four dominant categories of delay factors were identified: (1) infrastructure constraints insufficient lane segregation, intersection delays, and limited signal priority; (2) operational inefficiencies including irregular headways, bus bunching, and extended dwell times; (3) managerial challenges such as weak scheduling practices and fragmented institutional governance; and (4) external influences including congestion spillover and peak-hour passenger surges. Commonly used performance indicators include on-time performance, headway regularity, travel speed, dwell time, and travel time index. Conclusion: Improving BRT reliability requires integrated approaches that combine technological optimization, data-driven scheduling, infrastructure enhancements, and institutional alignment. Practical Implications: These findings offer a targeted framework for improving operational resilience in Indonesian corridors, particularly the Trans Jateng Semarang–Bawen route.